Revisiting ‘Iddah: A Critical Analysis of Gender Equality in Indonesian Feminist Islamic Legal Discourse - Fuady Abdullah; Nova Anggraini Putri; Youssof Salhein (JURIS (Jurnal Ilmiah Syariah), 2023)
Feminist legal theory highlights the persistence of women's subordination within the prevailing legal framework and emphasizes the importance of legal mechanisms that promote women's emancipation and equality. So far, the discourse of feminist Islamic law in Indonesia has caused more rejection, particularly with the emergence of the Counter Legal Draf-Kompilasi Hukum Islam (CLD-KHI), which is considered contrary to Islamic law, one of which is in the provisions of 'iddah. This study seeks to examine and analyze the demand for gender equality in the 'iddah period as manifested in the CLD-KHI. Using a qualitative research approach emphasizing library-based research on the draft in question and the supporting writings, this study bases its content analysis on the theory of Maqāṣid al-Sharī'ah, with al-Shatibi as the primary source. The results of this study reveal an insufficiency in the justification of the plea for gender equality in the enforcement of 'iddah from the view of Maqāṣid al-Sharī'ah. From the conventional perspective of Islamic law, the principle of gender equality as a maqṣad does not have a solid foundation, so it leads to rejection rather than acceptance. Therefore, to bear fruit, any legislative effort in the field of Islamic law must be carefully shaped by methodologies and ethos derived primarily from its tradition.